2023
DOI: 10.1002/brb3.3169
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in the salience network of patients with amnesic mild cognitive impairment before and after repetitive transcranial magnetic stimulation

Abstract: BackgroundAmnestic mild cognitive impairment (aMCI) is considered to be the prodromal stage of Alzheimer's disease (AD). The precuneus (PCUN) may be an imaging marker for monitoring the progression of AD. Meanwhile, cognitive impairment in AD patients is closely related to functional connectivity (FC) changes in the salience network (SN). We hypothesize that there are specific neuroimaging biomarkers in the SN and that FC changes in aMCI patients after repetitive transcranial magnetic stimulation (rTMS) interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 84 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Cognitive changes induced by rTMS may be due not only to modulation of functional brain activity in the stimulated region, but also to indirect effects on other relevant or distant brain regions (Rossi et al, 2001). Prior studies have demonstrated that when the precuneus is stimulated via rTMS, cognitive function can be enhanced through the regulation of brain circuits' plasticity and the reorganization of brain networks; for example, the regulation of precuneus-hippocampal circuits and the salience network (Chen et al, 2020;Yuan et al, 2023). The brain's lateralization in neurodegenerative diseases is linked to cognition and disease progression, indicating that changed connectivity between the hemispheres could be a marker of cognitive decline (Stefanits et al, 2012;Frings et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive changes induced by rTMS may be due not only to modulation of functional brain activity in the stimulated region, but also to indirect effects on other relevant or distant brain regions (Rossi et al, 2001). Prior studies have demonstrated that when the precuneus is stimulated via rTMS, cognitive function can be enhanced through the regulation of brain circuits' plasticity and the reorganization of brain networks; for example, the regulation of precuneus-hippocampal circuits and the salience network (Chen et al, 2020;Yuan et al, 2023). The brain's lateralization in neurodegenerative diseases is linked to cognition and disease progression, indicating that changed connectivity between the hemispheres could be a marker of cognitive decline (Stefanits et al, 2012;Frings et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The intersection tip of two coil rings was placed at the Pz site to stimulate the Precuneus with the assistance of a 10-20 electroencephalogram system. The rTMS stimulation frequency was 10 Hz (Chen et al, 2020(Chen et al, , 2022Yuan et al, 2023). The Resting State Motor Threshold (RMT) is a measure obtained by stimulating the left motor cortex with the right hand's First Dorsal Interosseous (FDI) muscle in a relaxed state, causing at least 5 of the 10 single pulse stimuli recorded on electromyography to have a motor evoked potential amplitude greater than 50 μV, or at least 5 out of 10 single pulse stimuli to result in FDI twitching in the right hand.…”
Section: Intervention-rtms Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Each subject received this treatment once a day, five days a week (Monday to Friday), for a duration of two weeks per course of treatment. The entire procedure was repeated for a total of four weeks, equivalent to two treatment courses ( Chen et al, 2021 ; Yuan et al, 2023 ). Subsequently, imaging data acquisition and neuropsychological evaluation were performed for each subject.…”
Section: Methodsmentioning
confidence: 99%